2007
DOI: 10.1038/ni1477
|View full text |Cite
|
Sign up to set email alerts
|

IgEb immune complexes activate macrophages through FcγRIV binding

Abstract: Because functional analysis of Fc receptors (FcRs) relies heavily on mouse models, the identification of another Fcgamma receptor is particularly noteworthy. We demonstrate that FcgammaRIV, identified here as the mouse ortholog of primate FcgammaRIII, required association of the FcR gamma-chain for optimal expression and function on myeloid cells; its signaling potential was also enhanced by a cytoplasmic 'YEEP' motif that was able to recruit the adaptor molecule Crk-L and phosphatidylinositol-3-OH kinase. Une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 46 publications
6
84
1
Order By: Relevance
“…In contrast, blocking antibodies for the medium affinity receptor FcγRIV resulted in an impaired platelet clearance. Similar results were obtained in human ITP patients where blocking antibodies to FcγRIIIA, which is the human ortholog of murine FcγRIV [23,42], but not to human FcγRI were very efficient in blocking platelet depletion [43][44][45][46]. Thus, FcγRs are instrumental for IgG-mediated platelet depletion for murine and human ITP and are an attractive target for therapeutic intervention.…”
Section: Effector Pathways Involved In Murine Itpsupporting
confidence: 73%
See 2 more Smart Citations
“…In contrast, blocking antibodies for the medium affinity receptor FcγRIV resulted in an impaired platelet clearance. Similar results were obtained in human ITP patients where blocking antibodies to FcγRIIIA, which is the human ortholog of murine FcγRIV [23,42], but not to human FcγRI were very efficient in blocking platelet depletion [43][44][45][46]. Thus, FcγRs are instrumental for IgG-mediated platelet depletion for murine and human ITP and are an attractive target for therapeutic intervention.…”
Section: Effector Pathways Involved In Murine Itpsupporting
confidence: 73%
“…The problem here is that a lot of crucial information regarding the mechanism and players involved in IgG-mediated effects have only been identified recently and are still under investigation. For example, the mouse ortholog to human FcγRIIIA has only been identified 4 years ago and is still not fully characterized [42,51]. More importantly, monoclonal antibodies specific for all mouse-activating FcγRs have become available only recently.…”
Section: Effector Cells and Organs Involved In Murine (And Human) Itpmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). During the steady state, FcγRIV is expressed mainly on neutrophils, monocytes, and macrophages (14,15,18,19). To demonstrate deletion of FcγRIV on the protein level, we analyzed FcγRIV expression on neutrophils (expressing Ly6G) and monocytes (Ly6G negative, CD11b positive) in blood, spleen, and bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for these observations was afforded by the identification of the mouse activating FcγRIV, which can bind to IgG2a and IgG2b with intermediate affinity (15). On the basis of protein sequence, genomic localization, and functional studies, mouse FcγRIV seems to be the ortholog to human CD16A, although it has some unique features, such as the capacity to bind to IgE with low affinity, and varies in its cellular expression pattern compared to its human counterpart (14,15,18,19). Using blocking antibodies, it was demonstrated that FcγRIV was essentially involved in IgG2a-and IgG2b-dependent killing of B cells, melanoma metastasis in the lung, and phagocytosis of platelets and red blood cells (11,14,15,(20)(21)(22).…”
mentioning
confidence: 99%